Risks assessment at automotive manufacturing company and ergonomic working condition - Hamizatun, Mohd Fazi; N. M. Zuki, N. M.; Azizul Qayyum, Basri (IOP Publishing, 2019)
Manufacturing sectors are the major industrial sector which contribute to the development of the country. The automotive manufacturing industry is a global industry which has high competition all over the world and contribute in large amount of revenue to the country. From the review, the management of automotive industries faced a few problems relates to the assembly line and the workers. The workers are exposed to hazard which resulting from unsuitable tasks or inappropriate workplace. The purpose of the study is to identify the occupational risks at automotive manufacturing company and recommend the ergonomic working condition at the workplace. This study is carried out through interview session, observation, videotaping and assessment method using Rapid Upper Limb Assessment (RULA). Based on the findings, it shows that the subjects are exposed to extremely high risks and the changes need to be done immediately. The occupational risks will lead to the presence of WorkMusculoskeletal Disorders (WMSDs) which cause absenteeism, employee turnover and the production drops. There are a few factors which causes the occurrence of WMSDs which are repetitive tasks, awkward postures and strenuous physical load or force exertion. The implementation of ergonomics in the workplace is important to avoid the presence of WMSDs.